Lithium battery positive electrode and preparation method thereof and solid-state battery
Patent Information
- Application Number
- CN202411736322.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-11-29
AI Technical Summary
然而,固态聚合物电解质低的离子电导率和较差的力学性能导致其易被枝晶穿透,因而在很大程度上降低了电池的电化学性能
[0041] The lithium-ion battery cathode and its preparation method provided by this invention, along with solid-state batteries, utilize a three-dimensional current collector, allowing the cathode composite material to permeate into the three-dimensional framework. This interpenetration enables the cathode to conduct both electrons and ions. Simultaneously, the three-dimensional structure restricts the aggregation of active materials, maintaining their good dispersion during charge and discharge. This helps maintain the reactivity of the active materials and improves the battery's performance stability.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery technology, and more particularly to lithium battery cathodes, their preparation methods, and solid-state batteries. Background Technology
[0002] With the widespread use of portable electronic devices such as mobile phones, laptops, and tablets, higher demands are being placed on the energy density, battery life, and safety of batteries. Lithium metal batteries, due to their high theoretical specific energy, have become a potential choice to meet these requirements. This has driven the research and development of lithium metal battery cathode materials to improve the overall performance of batteries and meet the ever-growing energy demands of portable electronic devices.
[0003] In recent years, the electric vehicle market has shown a rapid growth trend. Electric vehicles require high-performance batteries to provide sufficient driving range and power, and the high energy density of lithium metal batteries makes them highly promising for application in the electric vehicle field. Therefore, in order to meet the battery performance requirements of electric vehicles, the research and development of lithium metal battery cathodes has become particularly important.
[0004] In terms of battery manufacturing processes and technologies, continuous improvements and innovations have also supported the development of lithium metal battery cathodes. For example, improving electrode preparation methods can increase the loading and utilization rate of cathode materials, and optimizing battery structural design can improve battery safety and stability.
[0005] Solid-state electrolytes in lithium-ion batteries can effectively address the safety issues associated with liquid electrolytes. Solid-state electrolytes also possess flame-retardant properties, significantly improving battery safety. Among these, solid polymer electrolytes are widely used in solid-state batteries due to their good flexibility and excellent electrode contact. However, the low ionic conductivity and poor mechanical properties of solid polymer electrolytes make them susceptible to dendrite penetration, thus significantly reducing the battery's electrochemical performance. Summary of the Invention
[0006] This invention aims to at least partially solve one of the technical problems in the prior art. Therefore, the object of this invention is to provide a lithium battery cathode, a method for preparing the same, and a solid-state battery.
[0007] Based on this, the present invention has the following technical solution: In a first aspect, the present invention provides a lithium battery cathode, comprising: a cathode composite material and a current collector having a three-dimensional porous structure; wherein the cathode composite material partially fills the pores of the three-dimensional skeleton of the current collector, and the three-dimensional skeleton comprises a polymer solid electrolyte.
[0008] This invention designs a current collector with a three-dimensional structure, allowing the cathode composite material to permeate into the three-dimensional framework, achieving both electron and ion conduction. Specifically, the aforementioned three-dimensional cathode material forms a continuous conductive network, enabling electrons to be efficiently transported from the current collector to various parts of the active material, reducing resistance and energy loss during electron transport. This facilitates rapid electron transport within the electrode. Furthermore, the abundant pores and surface structure within the three-dimensional porous cathode material provide ample space for lithium-ion storage, allowing the battery to store more electrical energy. Simultaneously, the three-dimensional structure restricts the aggregation of the active material, maintaining its good dispersion during charge and discharge, which helps preserve the reactivity of the active material and improves battery performance stability.
[0009] Preferably, the amount of the polymer solid electrolyte is less than the amount of the positive electrode composite material.
[0010] More preferably, the mass ratio of the polymer solid electrolyte to the positive electrode composite material is (3~4):(6~7).
[0011] The present invention finds that the amount of polymer solid electrolyte is less than the amount of positive electrode composite material to ensure that the active material layer can penetrate into the three-dimensional solid electrolyte layer as much as possible. The amount of solid electrolyte layer should not be too small, otherwise the provided three-dimensional structure layer will be less and the effect will not be obvious. By controlling the polymer solid electrolyte and the positive electrode composite material in the above-mentioned dosage relationship, a uniform three-dimensional positive electrode layer can be formed, so as to achieve the effect of conducting both electrons and ions.
[0012] In this invention, the three-dimensional skeleton of the current collector is generated by a polymer solid electrolyte. Specifically, those skilled in the art can use methods such as electrospinning or meltblowing to introduce the polymer solid electrolyte into the current collector layer to form a three-dimensional skeleton.
[0013] Preferably, a melt-blowing method is used to spray a material containing a polymer solid electrolyte onto the current collector to form the current collector with a three-dimensional porous structure.
[0014] In a preferred embodiment of the present invention, when the polymer solid electrolyte is sprayed onto the current collector using the meltblown method, the specific parameters include: the receiving angle of the transmission receiver to the meltblown filament bundle is 0~90°, the receiving distance is 10~60cm, the spinneret orifice diameter is 0.15~0.4mm, the compressed air temperature is 250~300℃, the meltblown temperature is 220℃~300℃, and the time is 2min~6min.
[0015] Preferably, the porosity of the three-dimensional skeleton is 40% to 80%, specifically 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or any two of the above values as endpoints.
[0016] This invention has found that, compared with other methods, the melt-blowing method can construct a three-dimensional skeleton, increase the specific surface area, shorten the process flow, form a uniform three-dimensional network, and is more conducive to controlling the porosity to achieve the above-mentioned porosity.
[0017] Preferably, the preparation method of the polymer solid electrolyte includes: mixing unsaturated sulfonate monomer, catalyst, lithium salt and first organic solvent, and carrying out a polymerization reaction at 60~80°C.
[0018] In this invention, the temperature of the polymerization reaction can be 60℃, 65℃, 70℃, 75℃, 80℃, or any range between any two of the above values.
[0019] Preferably, the unsaturated sulfonate monomer has the structure shown in general formula (I): (I); wherein R and R' are each independently, identically, or differently a fluorine atom, a hydroxyl group, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted C1-C6 alkoxy group, a substituted or unsubstituted C2-C6 alkenyl group, or a substituted or unsubstituted C... 6~ C 30 A group consisting of aryl groups or any of the above groups; R and R' bonds forming a ring, fused into a ring, or not forming a ring.
[0020] Preferably, the unsaturated sulfonate monomer includes one or more of 2-phenylethylenesulfonyl fluoride, 1,3-propanesulfonyl lactone, vinylbenzenesulfonic acid, allyl sulfonate, 2,2-difluorovinyl-4-methylbenzenesulfonate, and allyl p-toluenesulfonate.
[0021] The present invention discovers that by using the above-mentioned unsaturated sulfonate monomer in the system of the present invention, metal ions can be prevented from being deposited and precipitated by forming complexes with metal ions such as lithium ions, thereby suppressing the dendrite growth of the battery and the instability of the solid electrolyte interface, and improving the safety and cycle life of the battery.
[0022] More preferably, based on the mass of the cathode composite material, the amount of the unsaturated sulfonate monomer is 30wt%~50wt%, specifically it can be 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc., or a range of values with any two of the above values as endpoints.
[0023] Preferably, the lithium salt includes at least one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium di(oxalateborate), lithium di(fluorooxalateborate), and lithium trifluoromethanesulfonate.
[0024] More preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide and / or lithium dioxalateborate.
[0025] More preferably, based on the mass of the unsaturated sulfonate monomer, the amount of lithium salt is 30wt% to 60wt%, specifically 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, etc., or a range of values with any two of the above values as endpoints.
[0026] The present invention has found that the above-mentioned lithium salt is more conducive to reducing the side reactions between the solid electrolyte membrane and the positive electrode, thereby reducing the capacity decay of the battery during the charging and discharging process, extending the battery's service life, and further improving the overall performance of the battery.
[0027] Preferably, the catalyst comprises one or more of aluminum trichloride, palladium chloride, palladium acetate, nickel dichloride, boron trifluoride, triethylamine, ferric bromide, ferric chloride, titanium tetrachloride, and tin tetrachloride.
[0028] More preferably, based on the mass of the unsaturated sulfonate monomer, the amount of catalyst used is 0.1wt% to 5wt%, specifically 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, etc., or a range of values with any two of the above values as endpoints.
[0029] Preferably, the first organic solvent includes one or more of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinic anionyl nitrile, glutaronitrile, adiponitrile, heptacyanide, octanoic anionyl nitrile, azelaic anionyl nitrile, and sebacate.
[0030] Preferably, the polymerization time of the polymerization reaction is 3 to 6 hours.
[0031] Secondly, the present invention provides a method for preparing the lithium battery positive electrode, comprising: S1: The unsaturated sulfonate monomer, catalyst, lithium salt and first organic solvent are mixed and polymerized at 60~80℃ to obtain a mixture; S2: The mixture is sprayed onto the current collector using a melt-blowing method, and after drying, a current collector with a three-dimensional porous structure is obtained.
[0032] S3: Mix the positive electrode material, conductive agent, binder and second organic solvent, coat the resulting mixed slurry onto the three-dimensional current collector obtained in S2, and dry to obtain the lithium battery positive electrode.
[0033] Preferably, the first organic solvent includes one or more of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinic anionitrile, glutaronitrile, adiponitrile, heptacyanide, octanoic anionitrile, azelaic anionitrile, and sebacate; the second organic solvent includes N-methylpyrrolidone.
[0034] Preferably, the lithium salt includes at least one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium di(oxalateborate), lithium di(fluorooxalateborate), and lithium trifluoromethanesulfonate.
[0035] Preferably, the catalyst comprises one or more of aluminum trichloride, palladium chloride, palladium acetate, nickel dichloride, boron trifluoride, triethylamine, ferric bromide, ferric chloride, titanium tetrachloride, and tin tetrachloride.
[0036] In this invention, the positive electrode material can be one or more of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and lithium vanadium phosphate; the conductive agent can be one or more of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and carbon fiber; the binder can be one or more of polyvinylidene fluoride, polyamide resin, polyacrylonitrile, sodium carboxymethyl cellulose, and styrene-butadiene rubber. Those skilled in the art can select the appropriate material based on the specific circumstances, and no specific limitations are made here.
[0037] As a preferred embodiment of the present invention, the specific parameters for spraying the polymer solid electrolyte onto the current collector using the melt-blowing method in S2 include: the receiving angle of the transmission receiver to the meltblown filament bundle is 0~90°, the receiving distance is 10~60cm, the spinneret orifice diameter is 0.15~0.4mm, the compressed air temperature is 250~300℃, the melt-blowing temperature is 220℃~300℃, and the time is 2min~6min.
[0038] In a preferred embodiment of the present invention, the method for preparing the lithium battery positive electrode includes: S1: 2-Phenylacetyl sulfonate, aluminum trichloride, LiTFSI and the first organic solvent are mixed and polymerized at 60~80℃ to obtain a mixture; S2: The mixture is sprayed onto the current collector using a melt-blowing method, and after drying, a current collector with a three-dimensional porous structure is obtained.
[0039] S3: Mix the positive electrode material, conductive agent, binder and second organic solvent, coat the resulting mixed slurry onto the three-dimensional current collector obtained in S2, and dry it to obtain the lithium battery positive electrode; the mass ratio of the polymer solid electrolyte to the positive electrode composite material is (3~4):(6~7).
[0040] Thirdly, the present invention provides a solid-state battery, including the aforementioned lithium battery positive electrode.
[0041] The lithium-ion battery cathode and its preparation method provided by this invention, along with solid-state batteries, utilize a three-dimensional current collector, allowing the cathode composite material to permeate into the three-dimensional framework. This interpenetration enables the cathode to conduct both electrons and ions. Simultaneously, the three-dimensional structure restricts the aggregation of active materials, maintaining their good dispersion during charge and discharge. This helps maintain the reactivity of the active materials and improves the battery's performance stability. Detailed Implementation
[0042] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0043] Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0044] Example 1 This embodiment provides a lithium battery cathode, the preparation method of which includes the following steps: S1: Add 2g of 2-phenylethylenesulfonyl fluoride, 0.02g of aluminum trichloride, 1.2g of LiTFSI and 20mL of DMF to a reaction flask equipped with a magnetic stir bar, seal it and place it in an oil bath, and polymerize at 70℃ for 6h to obtain a mixture.
[0045] S2: The mixture is sprayed onto the current collector aluminum foil using the melt-blowing method. After drying, a current collector with a three-dimensional porous structure is obtained. The receiving angle of the transmission receiver to the melt-blown wire bundle is 60°, the receiving distance is 30 cm, the spinneret orifice diameter is 0.2 mm, the compressed air temperature is 260°C, the melt-blowing temperature is 240°C, the time is 4 minutes, and the porosity of the three-dimensional structure is 55%.
[0046] S3: Mix 4g NCM811, 0.5g SP, 0.5g PVDF5130, and 4mL NMP in a homogenizer until homogenized. Then coat the mixture onto the three-dimensional current collector obtained in S2. Dry the mixture using an infrared drying plate coater for 45 minutes, and then transfer it to a vacuum drying oven for overnight drying. The mass ratio of the polymer solid electrolyte in S1 to the positive electrode composite material in S3 is 3:7.
[0047] Example 2 This embodiment provides a lithium battery cathode, the preparation method of which differs from that of Example 1 only in that the mass ratio of the polymer solid electrolyte in S1 to the cathode composite material in S3 is 4:6.
[0048] Example 3 This embodiment provides a lithium battery cathode, the preparation method of which differs from the preparation method of Embodiment 1 only in that: in S2, the mixture is introduced into the current collector aluminum foil by electrospinning, and after drying, a current collector with a three-dimensional porous structure is obtained, wherein the melt-blowing temperature is 220°C, the time is 5 min, and the porosity of the three-dimensional structure is 50%.
[0049] Example 4 This embodiment provides a lithium battery cathode, the preparation method of which differs from that of Example 1 only in that the mass ratio of the polymer solid electrolyte in S1 to the cathode composite material in S3 is 1:1.
[0050] Example 5 This embodiment provides a lithium battery cathode, the preparation method of which differs from that of Example 1 only in that: in S1, 2-phenylethylene sulfonyl fluoride is replaced with an equal amount of allyl sulfonate.
[0051] Example 6 This embodiment provides a lithium battery cathode, the only difference between which is the preparation method of Example 1: in S1, 2-phenylethylenesulfonyl fluoride is replaced with an equal amount of vinylbenzenesulfonic acid.
[0052] Example 7 This embodiment provides a lithium battery cathode, the preparation method of which differs from that of Example 1 only in that: in S1, 2-phenylethylene sulfonyl fluoride is replaced with an equal amount of allyl p-toluenesulfonate.
[0053] Example 8 This embodiment provides a lithium battery cathode material, the preparation method of which differs from that of Example 1 only in that: in S1, 2-phenylethylenesulfonyl fluoride is replaced with an equal amount of 2-acrylamide-2,2-methylpropanesulfonic acid.
[0054] Example 9 This embodiment provides a lithium battery cathode, the preparation method of which includes the following steps: S1: Add 2g of 2-phenylethylenesulfonyl fluoride, 0.02g of boron trifluoride, 1.2g of LiTFSI and 20mL of NMP to a reaction flask equipped with a magnetic stir bar, seal it and place it in an oil bath, and polymerize at 70℃ for 6h to obtain a mixture.
[0055] S2: The mixture is sprayed onto the current collector aluminum foil using a melt-blowing method. After drying, a current collector with a three-dimensional porous structure is obtained. The melt-blowing temperature is 240°C and the time is 4 minutes. The porosity of the three-dimensional structure is 55%.
[0056] S3: Mix 4g NCM811, 0.5g SP, 0.5g PVDF5130, and 4mL NMP in a homogenizer until homogenized. Then coat the mixture onto the three-dimensional current collector obtained in S2. Dry the mixture using an infrared drying plate coater for 45 minutes, and then transfer it to a vacuum drying oven for overnight drying. The mass ratio of the polymer solid electrolyte in S1 to the positive electrode composite material in S3 is 3:7.
[0057] Example 10 This embodiment provides a lithium battery cathode, the only difference between which is the preparation method and that of Example 1: the lithium salt additive is replaced with an equal amount of lithium hexafluorophosphate.
[0058] Test case Assembling the lithium battery cathode obtained in the examples into a solid-state battery includes the following steps: 1. Ionic Conductivity: The polymer solid electrolyte membranes (CSEs) prepared above were assembled with two stainless steel electrodes (SS) to form an SS / CSEs / SS simulated cell for testing. The cell assembly process was carried out in a glove box with water and oxygen content both below 0.1 ppm. Electrochemical impedance spectroscopy (EIS) was performed at room temperature using a frequency range of 0.01 Hz to 106 Hz to measure the electrochemical impedance of the polymer solid electrolyte. The ionic conductivity of the prepared polymer solid electrolyte was calculated from the impedance data obtained from the EIS test.
[0059] 2. Cycle Stability: The polymer solid electrolyte sheets (CSEs) prepared above were combined with a ternary cathode and a lithium metal anode to form coin cells. All battery fabrication was performed inside a glove box. The batteries were subjected to charge-discharge cycle tests at a rate of 0.1C, and the decay of their discharge capacity was assessed.
[0060] The electrochemical performance of the above-mentioned solid-state battery was tested, and the results are shown in Table 1.
[0061] Table 1
[0062] According to Table 1, compared with Example 1, Examples 2 and 4 show that when the amount of polymer solid electrolyte is less than that of the cathode composite material, it helps to form a uniform three-dimensional cathode layer and improve the effect of conducting both electrons and ions. Example 3 uses electrospinning to construct a three-dimensional structure, which, compared with the melt-blowing method used in Example 1, will affect battery performance to some extent. This is because the melt-blowing method can construct a three-dimensional skeleton, increase the specific surface area, shorten the process flow, form a uniform three-dimensional network, and is more conducive to controlling the porosity to achieve the above-mentioned level. Examples 5-9, compared with Example 1, replaced the sulfonate monomers, solvents, catalysts, etc. in the preparation system. The results show that when using sulfonate monomers, solvents, catalysts, etc., within the scope of this invention, the ionic conductivity of the polymer solid electrolyte and the cycle stability of the final battery are comparable to those of Example 1. However, when using sulfonate monomers outside the scope of this invention, it will affect battery performance to some extent. Compared with Example 1, when the lithium salt additive was replaced with an equal amount of lithium hexafluorophosphate in Example 10, the precursor mixture prepared by lithium hexafluorophosphate was jelly-like due to its hygroscopic nature, which affected the melt-blowing effect and made it difficult to construct a good three-dimensional structure. Therefore, it would significantly affect the electrochemical performance of the battery.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium battery positive electrode, characterized in that, include: A positive electrode composite material and a current collector having a three-dimensional porous structure; wherein the positive electrode composite material partially fills the pores of the three-dimensional skeleton of the current collector, and the three-dimensional skeleton includes a polymer solid electrolyte; The preparation method of the polymer solid electrolyte includes: mixing unsaturated sulfonate monomers, catalysts, lithium salts and a first organic solvent, and carrying out a polymerization reaction at 60-80°C. The unsaturated sulfonate monomer is one or more of 2-phenylethylenesulfonyl fluoride and vinylbenzenesulfonic acid. The lithium salt is at least one or more of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium di(oxalate)borate, lithium di(fluorooxalate)borate, and lithium trifluoromethanesulfonate. The material containing polymer solid electrolyte is sprayed onto the current collector using the melt-blowing method to form the current collector with a three-dimensional porous structure. The specific melt-blowing parameters are as follows: the receiving angle of the transmission receiver to the melt-blown filament bundle is 0~90°, the receiving distance is 10~60cm, the spinneret orifice diameter is 0.15~0.4mm, the compressed air temperature is 250~300℃, the melt-blowing temperature is 220℃~300℃, and the time is 2min~6min. The porosity of the three-dimensional skeleton is 55%~80%.
2. The lithium battery positive electrode according to claim 1, characterized in that, The amount of the polymer solid electrolyte is less than the amount of the positive electrode composite material.
3. The lithium battery positive electrode according to claim 2, characterized in that, The mass ratio of the polymer solid electrolyte to the positive electrode composite material is (3~4):(6~7).
4. The lithium battery positive electrode according to claim 1, characterized in that, The catalyst includes one or more of aluminum trichloride, palladium chloride, palladium acetate, nickel dichloride, boron trifluoride, triethylamine, ferric bromide, ferric chloride, titanium tetrachloride, and tin tetrachloride; And / or, the first organic solvent includes one or more of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinic anionyl nitrile, adiponitrile, adiponitrile, heptacyanide, octanoic anionyl nitrile, azelaic anionyl nitrile, and sebacate.
5. The method for preparing the lithium battery positive electrode according to any one of claims 1 to 4, characterized in that, include: S1: The unsaturated sulfonate monomer, catalyst, lithium salt and first organic solvent are mixed and polymerized at 60~80℃ to obtain a mixture; S2: The mixture is sprayed onto the current collector using a melt-blowing method, and after drying, a current collector with a three-dimensional porous structure is obtained; S3: Mix the positive electrode material, conductive agent, binder and second organic solvent, coat the resulting mixed slurry onto the three-dimensional current collector obtained in step S2, and dry to obtain the lithium battery positive electrode.
6. The method for preparing a lithium battery positive electrode according to claim 5, characterized in that, The lithium salt is at least one or more of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium di(oxalate)borate, lithium di(fluorooxalate)borate, and lithium trifluoromethanesulfonate.
7. The method for preparing a lithium battery positive electrode according to claim 5, characterized in that, The first organic solvent includes one or more of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinic anionitrile, glutaronitrile, adiponitrile, heptacyanide, octanoic anionitrile, azelaic anionitrile, and sebacate; the second organic solvent includes N-methylpyrrolidone.
8. The method for preparing a lithium battery positive electrode according to claim 5, characterized in that, Based on the mass of the unsaturated sulfonate monomer, the amount of lithium salt used is 30wt% to 60wt%.
9. The method for preparing a lithium battery positive electrode according to claim 5, characterized in that, The catalyst includes one or more of aluminum trichloride, palladium chloride, palladium acetate, nickel dichloride, boron trifluoride, triethylamine, ferric bromide, ferric chloride, titanium tetrachloride, and tin tetrachloride.
10. A solid-state battery, characterized in that, Includes the lithium battery positive electrode as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Composite positive pole piece, preparation method thereof and all-solid-state lithium ion battery
CN111900456A
Oxide solid electrolyte membrane, preparation method thereof and solid-state battery containing oxide solid electrolyte membrane
CN112436182A
Preparation and application of polysultone-based polymer electrolyte
CN115000504A